'Living with Teenagers': feasibility study of a peer-led parenting intervention for socially disadvantaged families with adolescent children. Issue 8 (23rd April 2014) - Michelson, Daniel; Ben-Zion, Ilan; James, Alana I; Draper, Lucy; Penney, Caroline; Day, Crispin
Abstract : Objective: To develop and test the feasibility of a peer-led parenting intervention for parents of adolescent children. Design: Formative evaluation using a mixed-method cohort design. Setting: Socially deprived community sites in London, UK. Participants: Parents seeking help with managing behavioural difficulties of an index adolescent child (aged 11–17 years). Intervention: A structured, group-based intervention ('Living with Teenagers') delivered by trained peer facilitators. Main outcome measures: We assessed feasibility in terms of uptake and completion rates (% parents completing ≥5 sessions); social validity (assessed by service satisfaction measure and participant interviews); and potential for impact (assessed by parent-reported measures of adolescent behaviour and mental health, parenting satisfaction, expressed emotion, and disciplinary practices). Results: Participants (n=41) were predominately (79%) from minority ethnic backgrounds and nearly half were lone parents. Most had not previously accessed a structured parenting programme. The completion rate was 71%. Significant changes (p<0.05) were observed in reduced parental concern about adolescent problems, increased parenting satisfaction and less negative expressed emotion. There were non-significant changes in disciplinary practices and adolescent mental health. Participants were highly satisfied with their service experience and endorsed the acceptability of the intervention's content, materials and peer-led format, while suggesting an expanded number of sessions and more skills practice and demonstrations. Conclusions: Peer-led parenting groups are feasible and potentially effective for supporting parents of adolescents living in socially disadvantaged communities. These findings warrant more rigorous testing under controlled conditions.